Identification of Nrf2 Activators from the Roots of Valeriana officinalis - Afzal, Sualiha; Zhou, Xian; Or, King; Raju, Ritesh; Münch, Gerald (Planta Medica, 2022)
Various age-related chronic diseases have been linked to oxidative stress. The cellular antioxidant response pathway is regulated by the transcription factor nuclear erythroid factor 2. Therefore, plant-derived nuclear erythroid factor 2 activators might be useful therapeutics to stimulate the bodyʼs defense mechanisms. Our study focused on the discovery of potent nuclear erythroid factor 2 activators from medicinal plants. Initially, a variety of medicinal plant extracts were screened for nuclear erythroid factor 2 activity using a nuclear erythroid factor 2 luciferase reporter cell line. Among these, Valerian (Valeriana officinalis) root was identified as a potent candidate. Sequential extraction and bioassay-guided fractionation led to the isolation of four nuclear erythroid factor 2-active compounds, which were structurally identified by NMR and LC/HRMS as the known compounds isovaltrate, valtrate, jatamanvaltrate-P, and valerenic acid. These four compounds were then tested in relevant biological assays. Firstly, their effects on the expression of glutathione S-transferase, glutamate–cysteine ligase catalytic subunit, glutathione peroxidase, and heme oxygenase 1 were determined in HepG2 cells. Glutathione S-transferase P1 and glutamate–cysteine ligase catalytic subunit were upregulated by isovaltrate, valtrate, and jatamanvaltrate-P, while heme oxygenase 1 was upregulated by isovaltrate, jatamanvaltrate-P, and valerenic acid. The four compounds also increased the levels of glutathione and its metabolite, CysGly. As glutathione aids in the detoxification of hydrogen peroxide, cytoprotective effects of these four nuclear erythroid factor 2 activators against hydrogen peroxide toxicity were investigated, and indeed, the compounds significantly improved cell survival. This study provides evidence that four valepotriates from the roots of V. officinalis are activators of nuclear erythroid factor 2-mediated antioxidant and detoxification pathways. Our data might expand the medical use of this plant beyond its current application as a sleep aid.
Keywords: Valeriana officinalis; valepotriates; antioxidants; Nrf2 activators; Caprifoliaceae